Positive difference operators of any preassigned approximation order for the second derivative - Terteryan, A.A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Difference operators are stuied, constructed by the method of block approximation for the differential operator -d^2/dt^2 with homogeneous first boundary conditions. For separators of any order of approximation the positivity property is established.